Mutual Interference between Cytomegalovirus and Reconstitution of Protective Immunity after Hematopoietic Cell Transplantation - Reddehase, Matthias J. (Frontiers in Immunology, 2016)
Hematopoietic cell transplantation (HCT) is a therapy option for aggressive forms of hematopoietic malignancies that are resistant to standard antitumoral therapies. Hematoablative treatment preceding HCT, however, opens a ‘window of opportunity’ for latent cytomegalovirus (CMV) by releasing it from immune control with the consequence of reactivation of productive viral gene expression and recurrence of infectious virus. A ‘window of opportunity’ for the virus represents a ‘window of risk’ for the patient. In the interim between HCT and reconstitution of antiviral immunity, primarily mediated by CD8+ T cells, initially low amounts of reactivated virus can expand exponentially, disseminate to essentially all organs, and cause multiple organ CMV disease, with interstitial pneumonia (CMV-IP) representing the most severe clinical manifestation. Here I will review predictions originally made in the mouse model of experimental HCT and murine CMV infection, some of which have already paved the way to translational preclinical research and promising clinical trials of a pre-emptive cytoimmunotherapy of human CMV disease. Specifically, the mouse model has been pivotal in providing ‘proof of concept’ for preventing CMV disease after HCT by adoptive transfer of preselected, virus epitope-specific effector and memory CD8+ T cells bridging the critical interim. CMV, however, is not a ‘passive antigen’ but is a pathogen that actively interferes with the reconstitution of protective immunity by infecting bone marrow stromal cells that otherwise form niches for hematopoiesis by providing the structural microenvironment and by producing hematopoietically active cytokines, the hemopoietins. Depending on the precise conditions of HCT, reduced homing of transplanted hematopoietic stem- and progenitor cells to infected bone marrow stroma and impaired colony growth and lineage differentiation can lead to ‘graft failure’. In consequence, uncontrolled virus spread causes morbidity and mortality. In the race between viral bone marrow pathology and reconstitution of antiviral immunity following HCT, exogenous reconstitution of virus-specific CD8+ T cells by adoptive cell transfer as an interventional strategy can turn the balance towards control of CMV.